Integrated and differential fiducial cross-section measurements for the vector boson fusion production of the Higgs boson in the H→WW[ast]→eνμν decay channel at 13 TeV with the ATLAS detector - Aad, Georges; Baltes, Lisa Marie; Bartels, Falk; Czurylo, Marta; Dittmeier, Sebastian; Dunford, Monica; Franchino, Silvia; Junkermann, Thomas; Klassen, Martin; Mkrtchyan, Tigran; Ott, Philipp; Rassloff, Damir Fabrice; et al. (Physical review, 2023)
The vector-boson production cross section for the Higgs boson decay in the H→WW∗→eνμν channel is measured as a function of kinematic observables sensitive to the Higgs boson production and decay properties as well as integrated in a fiducial phase space. The analysis is performed using the proton-proton collision data collected by the ATLAS detector in Run 2 of the LHC at √s=13 TeV center-of-mass energy, corresponding to an integrated luminosity of 139 fb−1. The different flavor final state is studied by selecting an electron and a muon originating from a pair of W bosons and compatible with the Higgs boson decay. The data are corrected for the effects of detector inefficiency and resolution, and the measurements are compared with different state-of-the-art theoretical predictions. The differential cross sections are used to constrain anomalous interactions described by dimension-six operators in an effective field theory.